Strategies For Strengthening Community Engagement (Civic Engangement) Tuban East Java In Building Ecological Citizenship By Mangrove Center Foundation - Dwi Wahyu Kartikasari; Fitria Anjar Sari; Djoko Apriono; Yudi Supijanto; Suttrisno Suttrisno (FKIP, Universitas Palangka Raya, 2024)
The purpose of this study was to determine the strategy of the mangrove center Foundation in strengthening Tuban community involvement into ecological citizenship. This research is based on the issue of environmental damage that is increasing every year, as well as the handling of environmental damage related to the government, related institutions, and the community. This study uses qualitative methods with a case study approach. The results found from this study is the role of the Mangrove Center as part of the civic community in combating environmental damage through strengthening environmental awareness in the community and related institutions. The participation starts from socialization, providing examples, and working together with the Environment Agency and local government agencies.